Правове регулювання україно-іспанських відносин у сфері економічного та промислового співробітництва - Князєва, Д.О. (Альманах права, 2012)
Стаття присвячена дослідженню характерних особливостей міжнародно-правового регулювання співробітництва вищевказаних держав у сфері економічного та промислового співробітництва. Статья посвящена исследованию характерных особенностей международно-правового регулирования указанных государств в сфере экономического и промышленного сотрудничества. The article investigates the characteristics of international legal regulation of these states in the sphere of economic and industrial cooperation. It is noted that the balance of relations between Spain and the former CIS countries is very poor. This is especially
true in Ukraine. However, these relationships are very useful for both countries, since relations between Ukraine and the EU are quite privileged, and it can raise the status of political relations with this country. However, there is a network of economic relations is very slow. The basic legal act in this regard is the Agreement on economic and industrial cooperation. The adoption of this Agreement, the parties pledged to promote bilateral cooperation in every way. Identified the following sectors of cooperation: industry, construction, natural resources, energy and investment. The agreement establishes the need for a special Joint Commission on economic and industrial cooperation. 08.07.2008 was held the first meeting of this committee, which identified such promising areas of cooperation: energy, agriculture, construction, tourism, etc.
In 2010 it was the second meeting of the said commission. It was devoted primarily on Spanish investments to Ukraine and on agriculture. Thus, we see the practical implementation of this Agreement into effect. However, the existing legal framework
is not perfect. To strengthen relations between Ukraine and Spain need to adopt an Agreement on the Limitation of double taxation.